A bibliometric analysis of 3D printing in endodontics - Karatekin, Anil Ozgun (Vojnosanitetski pregled, 2025)
Background/Aim. In recent years, owing to the development of the three-dimensional (3D) printing method, managing complex clinical cases and educational and standardized experimental models has become possible, with a sharp increase in publications from 2018. The aim of this study was to reveal the bibliometric analysis and trends of the studies published in the field of the use of 3D printing in endodontics in the last 10 years. Methods. Studies published between 2014 and 2023 were accessed in the Web of Science Core Collection database, and the data obtained were examined with bibliometric analysis in terms of countries, journals, publication years, publication numbers, publication types, topic tendencies, and citation analysis. Results. A total of 128 papers were included in the study. The retrieved papers received an average of 13.59% of citations per publication. The first three countries with the highest number of publications were the People’s Republic of China, the United States of America (USA), and Germany. At the same time, the first three countries with the highest number of citations were Germany, Switzerland, and USA. In the co-authorship analyses, it can be seen that the highest total link strength is between Germany and Switzerland, while the USA is the country with the highest number of co-authorships. The top five keywords with the highest total link strength were “3D printing”, “guided endodontics”, “endodontics”, “root canal treatments”, and cone-beam computed tomography or “CBCT”. Conclusion. To our knowledge, this study is the first bibliometric analysis of worldwide research on the use of 3D printing in the endodontic field. Such analyses need to be conducted regularly to closely monitor the development of this research field.